2011
DOI: 10.3109/1061186x.2011.622395
|View full text |Cite
|
Sign up to set email alerts
|

Oral microparticulate vaccine for melanoma using M-cell targeting

Abstract: Cancer vaccines are limited in their use, because of their inability to mount a robust anti-tumor immune response. Thus, targeting M-cells in the small intestine, which are responsible for entry of many pathogens, will be an attractive way to elicit a strong immune response toward particulate antigens. Therefore, in the present investigation, we demonstrated that efficient oral vaccination against melanoma antigens could be accomplished by incorporating the antigens in an albumin-based microparticle with a lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The mucosal route of entry and initiation of primary immune response is well established where pathogens and other invasive microbes enter the host system via regions in the small intestine. Bernadette et al 128 described a study wherein they formulated a novel prophylactic oral microparticulate vaccine composed of whole cell lysate for melanoma using the spray-drying technique. Surface morphology of microparticles evaluated by scanning electron microscopy (SEM) showed that the particles had a spherical surface with a size distribution of around 1 to 2 mm ( Figure 5.8).…”
Section: Melanoma Cancer Vaccinementioning
confidence: 99%
“…The mucosal route of entry and initiation of primary immune response is well established where pathogens and other invasive microbes enter the host system via regions in the small intestine. Bernadette et al 128 described a study wherein they formulated a novel prophylactic oral microparticulate vaccine composed of whole cell lysate for melanoma using the spray-drying technique. Surface morphology of microparticles evaluated by scanning electron microscopy (SEM) showed that the particles had a spherical surface with a size distribution of around 1 to 2 mm ( Figure 5.8).…”
Section: Melanoma Cancer Vaccinementioning
confidence: 99%
“…M cells particularly adhere to microparticles and actively transport them into Peyer’s patches in intestines. Therefore, ligands targeting M cells, incorporated into microparticles would be a promising approach to increase the efficacy of uptake of oral vaccines in intestines [103,152]. Challenges in developing oral vaccination in humans include the requirement for higher doses of vaccines and lower efficacy in inducing systemic antibody responses [95] in contrast to studies in mice [101,112,153].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…Langerhans cells are dendritic cells that activate T cells and induce a strong immune response and occupy around 20% of the skin's area. On the other hand, M-cells are the microfold cells, which act as sampling ports for any foreign entities encountered in the small intestine upon oral administration [18][19][20][21][22][23]. These M cells house various dendritic cells and immune cells in them.…”
Section: Introductionmentioning
confidence: 99%
“…Several others have mentioned their usage for oral sustained or controlled release delivery [31,32]. To target the vaccine formulation to M-cells in the Peyer's patches of the intestine upon oral delivery, M-cell targeting agent, Aleuria aurantia lectin (AAL) was used in the formulation [15,20,21]. In addition, immunostimulatory molecules such as IL-2 and IL-12 were added in order to enhance the overall potency of the formulated vaccines.…”
Section: Introductionmentioning
confidence: 99%